2022
DOI: 10.1038/s41589-022-01153-w
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-driven modifications of lipoic arm inhibit α-ketoacid dehydrogenases

Abstract: Pyruvate dehydrogenase complex (PDHC) and oxoglutarate dehydrogenase complex (OGDC), which belong to the mitochondrial α-ketoacid dehydrogenase family, play crucial roles in cellular metabolism. These multi-subunit enzyme complexes use lipoic arms covalently attached to their E2 subunits to transfer an acyl group to coenzyme A (CoA). Here, we report a novel mechanism capable of substantially inhibiting PDHC and OGDC: reactive nitrogen species (RNS) can covalently modify the thiols on their lipoic arms, generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…To perturb NO level in macrophages, we took two approaches. First, to limit NO accumulation in macrophages upon stimulation, we used BMDMs isolated from Nos2 -/- mice, which do not produce NO upon stimulation (Seim et al, 2023). The efficacy is confirmed by the lack of citrulline (the other product of iNOS) accumulation over time after stimulation (Supplementary Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perturb NO level in macrophages, we took two approaches. First, to limit NO accumulation in macrophages upon stimulation, we used BMDMs isolated from Nos2 -/- mice, which do not produce NO upon stimulation (Seim et al, 2023). The efficacy is confirmed by the lack of citrulline (the other product of iNOS) accumulation over time after stimulation (Supplementary Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…XOR: GAAGACGTTGCGTTTTGAAG HPRT: ACGGGGGACATAAAAGTTAT Nos2 -/-RAW 264.7 cells that were used were previously generated as described (Seim et al, 2023).…”
Section: Generation Of Knock Out Cell Linesmentioning
confidence: 99%
“…It was later discovered PDHc and KGDHc are deactivated by lipid peroxidation end-product, 4-hydroxy-2-nonenal (4-HNE), and mtH 2 O 2 [ 16 , 79 , 128 , 129 ]. This deactivation occurred through the redox modification of the vicinal thiols in the lipoic acid residue to the E2 subunit of PDHc and KGDHc [ 47 , [130] , [131] , [132] ]. Oxidation of the vicinal lipoic acid thiols in KDHc by mtH 2 O 2 to a corresponding sulfenic acid (P–SOH) can also result in irreversible oxidation to corresponding sulfinic (P–SO 2 H) and sulfonic acids (P–SO 3 H) when mtH 2 O 2 is high ( Fig.…”
Section: Kdhc Are Mto 2 •- /Mth ...mentioning
confidence: 99%
“…However, in a separate study, it was shown BCKDHc does not undergo S-glutathionylation [ 149 ]. PDHc, KGDHc, and BCKDHc have also been found to undergo S-nitrosylation in several studies [ 131 , 132 , 150 ]. Like S-glutathionylation, the S-nitrosylation shuts down the activity of the KDHc but also likely protects the enzymes from irreversible deactivation through the overoxidation of the lipoic acid vicinal thiols.…”
Section: Kdhc Are Mto 2 •- /Mth ...mentioning
confidence: 99%
“…Concerning the ETC and TCA cycle, these enzymes include aconitase, the α-ketoglutarate dehydrogenase complex and succinate dehydrogenase, while in the case of fatty acid catabolism, long-chain and short-chain acyl-CoA dehydrogenase and enoyl-CoA hydratase, carnitine palmitoyl transferase 2 and flavoprotein dehydrogenase belong to the enzymes that are inhibited [ 87 ]. A recent study revealed a novel mechanism with which RNS generated by macrophages can render inactive α-ketoacid dehydrogenases (including pyruvate dehydrogenase complex and α-ketoglutarate dehydrogenase complex) [ 99 ]. In this study, it was shown that the lipoid arm of α-ketoacid dehydrogenase can be modified by RNS-mediated thiol modifications, and in turn, the acyl-transfer activity of the lipoid arm is blocked leading to the inhibition of pyruvate dehydrogenase complex and α-ketoglutarate dehydrogenase complex.…”
Section: Protein S-nitrosylationmentioning
confidence: 99%